Demystifying peer reviewing: Building capacity, capability and community in project scholarship - Zerjav, Vedran; Martinsuo, Miia; Papadonikolaki, Eleni; Huemann, Martina (Elsevier BV, 2026)
Peer review remains a cornerstone of academic publishing, ensuring rigour, relevance, and integrity of scholarly work. As the project management field is growing, it increasingly requires expansion of capacity and capabilities to ensure new ideas, and balance rigour and relevance. In this editorial, we discuss peer reviewing as an opportunity to grow capability, capacity, and community to demystify academic publishing.  We also introduce practical experiences from the recent International Journal of Project Management (IJPM) Reviewer Development Programme and reflect its key learnings to drive the development of a more inclusive and developmental review culture in project management.